A study on cost analysis of various oral hypoglycemic Agents available in india - DR.PREETHA SELVA; DR.V.KRISHNAN (International Journal of Pharma and Bio Sciences, 2017)
To find out the different oral hypoglycaemic agents available in India either singly or in combination under different brands, comparing their cost and calculating the percentage variation in cost. Method-List of all oral hypoglycaemic drugs available in India was taken from CIMS and IDR 2016 version. The different formulations manufactured by different pharmaceutical companies were obtained and their costs were compared. Percentage variation in cost of each drug marketed under different brands was calculated. Totally 17 anti diabetic drugs (10 single drug therapies & 7 combination drugs) were analyzed. These drugs are available in 341 formulations being marketed in India with different brand names and prices. Glipizide 2.5 mg was the least expensive single drug therapy. Among the combination therapies available glibenclamide+ metformin combination was the cheapest of all. The drug showing the least percentage of cost variation when used singly is metformin 250 mg. Metformin 500 mg shows the maximum percentage of cost variation. Among the combination therapies available gliclazide + metformin and glimeperide + metformin shows the least and highest percentage of variation in cost respectively. The health care providers should be aware of the various formulations available along with the pricing of drugs to enable them to choose the best cost effective drug which will prevent economic burden to the society and maintain compliance of the patients.